946 Peril in paradise: an epidemiological analysis of injuries in tropical north Queensland, Australia. (1st September 2016) - Watt, Kerrianne; Mills, Jane; Neighbour, Nicky; Harris, Linton; Franklin, Richard; Beaton, Neil; Wyatt, Don
Abstract : Background: Tropical North Queensland is a popular national and international tourist destination in Queensland, Australia. Approximately 2000000 tourists visit the region annually; there are approximately 150000 residents. Tourists and residents participate in activities like bushwalking in the surrounding rainforests, swimming/snorkelling/diving in the Great Barrier Reef, and a range of adventure sports. Consequently, exposure to a range of venomous creatures and other risky situations is higher than usual. Cairns Hospital is the main public hospital in the region; the annual throughput of the Emergency Department (ED) is 60000 presentations. The purpose of this study was to investigate the epidemiological characteristics of the injuries treated at Cairns Hospital ED over a 4 yr period. Methods: Data were obtained regarding all injury presentations at the Cairns Hospital Emergency Department over 4 yrs (1 st Jan 2010–31 st Dec 2013). Descriptive analyses were completed to determine the epidemiological characteristics of these injury presentations (via SPSS). Results: There were 55, 475 injury episodes treated at the Cairns Hospital ED over the study period, comprising 25.73% of all presentations to the ED. Injury was the leading cause for ED presentation over the 4 yr period. The proportion of injury presentations did not vary significantly over time. 15%of injury episodes involved tourists (3.6% interstate, 3.7% international, 7.5% from elsewhere in Queensland). Interstate tourists and tourists from elsewhere in Queensland were significantly more likely to be hospitalised as a consequence of their injury than residents of North Queensland (29% vs 22%; p < 0.001), and international tourists were less likely to require hospitalisation (17%). Every year from 2010–2013, approximately 75 patients were treated for poisoning by venomous creatures. The majority of these were residents of Far North Queensland, but 10 international and 7 interstate tourists per year experienced poisoning of this nature. Mechanism and patterns of injury (e.g., most frequent injuries sustained) in relation to tourist status, age group and gender will be presented in further detail at the conference. Conclusions: This is a descriptive epidemiological study of injuries sustained by residents and tourists of Far North Queensland. These data can be used to inform injury prevention strategies, and to adequately prepare visitors and residents for safe enjoyment of the region.